1998
DOI: 10.1093/qjmed/91.7.505
|View full text |Cite
|
Sign up to set email alerts
|

Causes, management and morbidity of acute hypoglycaemia in adults requiring hospital admission

Abstract: In the community, acute hypoglycaemia is commonly caused by therapies for diabetes mellitus or the excessive consumption of alcohol. Although most episodes do not require admission to hospital, little information is available on the causes and outcome of those that do. We retrospectively surveyed adult patients admitted to a large urban teaching hospital with acute hypoglycaemia in a 12-month period, identifying 56 admissions of 51 patients. Forty-one had diabetes mellitus, 33 (80%) of whom were receiving trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 1 publication
2
27
0
1
Order By: Relevance
“…It is most common in those with diabetes receiving insulin or oral hypoglycaemics, but also occurs in patients with liver disease, renal insufficiency, congestive heart failure, sepsis, malnutrition, or cancer 9 . Factitious or surreptitious use of insulin or sulfonylurea drugs is probably the most common cause of hypoglycaemia among patients who do not have diabetes 10 .…”
Section: Discussionmentioning
confidence: 99%
“…It is most common in those with diabetes receiving insulin or oral hypoglycaemics, but also occurs in patients with liver disease, renal insufficiency, congestive heart failure, sepsis, malnutrition, or cancer 9 . Factitious or surreptitious use of insulin or sulfonylurea drugs is probably the most common cause of hypoglycaemia among patients who do not have diabetes 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalization is required in a minority of patients, usually for observation of neurologic signs during hypoglycemia, such as seizures, obtundation, coma, or focal neurologic signs. The need for hospitalization arises most commonly in diabetic patients, although hypoglycemia is frequently identified in patients with malnutrition and associated alcohol consumption, mental illness, or severe underlying medical illness [Hart & Frier, 1998]. Hypoglycemia occurs in 1.2% of hospitalized patients and is of somewhat more diverse etiology [Fischer et al, 1986].…”
Section: Hypoglycemia In Diabetes Mellitusmentioning
confidence: 99%
“…found that 14% of admissions of DKAwere cocaine users. Hart and Frier [15] found 19% of diabetics were admitted with severe hypoglycemia due to alcohol intake.…”
Section: Prevalence Of Nutritional Disorders In Chronic Alcohol and Dmentioning
confidence: 99%